Pelatihan Transformasi Digital: Strategi Konten untuk Pengenalan Yang Lebih Luas Pada Madrasah Diniyah As-Syamsuriyah - sundari, jenie; Yunita, Yunita; Laila, Kumi (Universitas Islam Madura, 2025)
. This community service program was carried out to support Madrasah Diniyah As-Syamsuriyah in utilizing digital transformation to expand its institutional visibility. The rapid growth of information technology requires educational institutions, including madrasahs, to adapt through effective communication and digital information dissemination strategies. The program was implemented through training sessions, mentoring, and hands-on practice in designing digital content strategies, covering planning, content creation, and distribution via social media platforms. The results demonstrated significant improvement in participants’ knowledge and skills in managing creative and engaging digital content that reflects the madrasah’s identity. Participants were also able to develop a content calendar and optimize digital platforms to broaden the outreach of information to the community. This initiative is expected to serve as a foundation for Madrasah Diniyah As-Syamsuriyah in building a positive image and strengthening its existence in the digital era, while reinforcing its role as a center of religious education relevant to contemporary developments.